Higher Dietary Inflammatory Index Scores Increase the Risk of Diabetes Mellitus: A Meta-Analysis and Systematic Review - Tan, Qing-Qing; Du, Xin-Yi; Gao, Chen-Lin; Xu, Yong (Frontiers in Endocrinology, 2021)
The relationship between Dietary Inflammatory Index (DII) scores and the risk of diabetes mellitus (DM) is unclear, therefore a systematic review and meta-analysis of the current published literature was conducted. Relevant studies published online (PubMed, Embase, and Web of Science) until February 1, 2021 were identified for review. The initial search yielded 13 reports, and after perusing their titles, abstracts, and full-texts 5 studies were deemed appropriate for inclusion in the systematic review and meta-analysis. Individuals with higher DII scores (representing a more proinflammatory diet) had a higher risk of DM (pooled odds ratio 1.32, 95% confidence interval 1.01–1.72, I2 58.6%, p < 0.05). Although the current meta-analysis indicated a trend toward a positive association between DII and DM, further evidence—especially from larger prospective studies in different countries—is needed to clarify this association.